Badminton racket deflection, comparison between rigid versus flexible according to different strokes - Phomsoupha, M.; Ibrahime, S.; Laffaye, G. (International Journal of Racket Sports Science, 2024)
Badminton shuttlecock generate the highest projectile velocity among all sports. To deliver a powerful stroke, the design of a badminton racket is primordial, especially the deflection on the shaft. The purpose of the study was to analyse the gain of racket deflection compares with a rigid racket during four different strokes. Eight national and international standard badminton players participated in this study and performed a drop, a clear, a smash and a full smash. Six reflective markers were affixed to the racket and were recorded with Vicon cameras capture system set. Results showed racket deflection increased racket head velocity by shaft deflection by +13.2% during a full smash and a typical time around 60 ms during which the player accelerates the racket head. The gain obtained between head velocity related to the handle by +74% during a full smash. The deflection is caused by the relation between player ability, racket mass repartition and stiffness properties of the shaft. Finding suggest players should choose a racket with their badminton stroke pattern, especially the timing of the preparation phase before the impact with the shuttlecock to obtain the higher deflection and the best energy restitution during the impact.